Temporal and Spatial Differences in Carbon Emissions and Carbon Neutrality Caused by Land Use Changes in Fujian Province - Zhou Ping; Chen Songlin; Li Jing; Li Chenxin (Shuitu baochi tongbao)
[Objective] The differences in carbon emissions and carbon neutrality due to land use changes were analyzed in order to provide a basis for formulating low-carbon development policies in various regions according to net carbon emissions. [Methods] Based on data for land use and energy consumption in Fujian Province from 2005 to 2020, carbon emissions and carbon neutrality value calculation models were constructed to calculate the carbon emissions and carbon neutrality values for different cities in different periods. [Results] ① The net carbon emissions for land use changes in Fujian Province showed an obvious growth trend, and the growth rate was initially fast and then slowed. Construction land was the main carbon source, and its carbon emissions increased by 34.08 million tons. Forest land was the main carbon sink, and its carbon absorption decreased by nearly 30 000 tons. ② The areas with high net carbon emissions were mainly located in Fuzhou, Quanzhou, and Zhangzhou cities. These areas exhibited high carbon emissions and low carbon neutrality rate. The areas with low net carbon emissions were mainly located in Nanping City where low carbon emissions and high carbon neutrality rate were observed. Except for Xiamen City, the intensity of net carbon emissions in each city was similar to the spatial distribution of net carbon emissions. ③ The carbon neutrality value was highly similar to the spatial distribution of net carbon emissions in each city. The high carbon neutrality areas were mainly in Fuzhou City and Quanzhou City where economic development level was high and net carbon emission was large, while the compensation area was mainly found in Nanping City where economic development level was low and net carbon emission was small. [Conclusion] In order to achieve regional coordination and low-carbon development, it is necessary to constantly improve the carbon neutrality mechanism and to rely on carbon neutrality to promote coordinated development of regional low-carbon policies.